Food and nutrient intake at 1 year of age in Northern Sweden: results from the Swedish NICE birth cohort - Stråvik, Mia; Kampouri, Mariza; Gustin, Klara; Sandin, Anna; Wold, Agnes E.; Barman, Malin; Sandberg, Ann-Sofie (Frontiers in Nutrition, 2025)
Dietary habits and nutrient intake early in life are important for long-term health. Here, we examine food and nutrient intake at 1 year of age in the Swedish NICE (Nutritional impact on Immunological maturation during Childhood in relation to the Environment) birth cohort in relation to dietary guidelines and family characteristics. Dietary data was collected using a web-based semi-quantitative food frequency questionnaire (TodMeal-Q). Our findings show that intakes of critical micronutrients such as selenium, iodine, and iron were substantially below recommended levels. Also, the dietary patterns observed, characterized by higher protein and lower fat intake compared to recommendations, highlight the need for nutritional guidance to mitigate long-term health risks. Moreover, family dynamics, including the presence of siblings and maternal smoking habits, should be considered in designing effective dietary interventions, as these factors may be indicative of the context in which feeding practices are established.